Mangroves as a Coastal Protection of Local Economic Activities from Hurricanes in the Caribbean : 360° Resilience Background Paper - Miranda, Juan Jose; Gunasekera, Rashmin; Butron, Luigi; Pantoja, Chrissie; Daniell, James; Brand, Johannes (Washington, DC: World Bank, 2021)
In recent decades, hurricane frequency and intensity have increased in the Caribbean basin. From 2000 to 2012, more than 100 hurricanes impacted lives, infrastructure, gross domestic product, and natural environments along the coastal shorelines. Recent academic references mention that the dense root system of mangrove forests might mitigate the impact of hurricanes, which would help stabilize the coastline and prevents erosion from waves and storms. Many tropical mangroves are found on the coasts of Caribbean islands, unfortunately, these wetland ecosystems have been cleared at a rate of one percent per year since the nineties by climatic and anthropogenic events. Given this critical context, this study quantifies the causal effects hurricane windstorms on local economic activity, using as a proxy nightlights in the Caribbean region at the highest spatial resolution data available (1 square kilometer), and then measure the level of mangrove natural protection against the impact of hurricanes, employing different widths of the mangroves belt, which leads to a broader socio-economic and environmental perspective study. The results suggest that major hurricanes show negative effects of approximately two percent in nightlights and even a greater negative impact of sixteen percent in storm surge prone areas. However, the presence of mangroves on the coast minimizes the impact of hurricanes, shows a reduction of nightlights between one and six percent. The paper contributes to the literature of natural coastal protection against natural disasters by providing robust estimates of the causal effects of major hurricanes windstorms in the Caribbean, producing regional evidence that could improve targeting of environmental policies and disaster risk management toward those most impacted islands.